Application of Error-compensation in the Mapping of Cam Mechanism - Zhu Lei; Fu Yanming; Zhou Xuanyan; Fu Haoyun (Jixie chuandong)
The data preprocessing method of the cam profile and data error compensation theory of the cam profile in the reverse design cam mechanism are introduced.According to the introduction of cam,the data of discrete points of the actual cam profile line is mapping,the possible’noise point’is removed,and the cam theoretical profile equation is deduced.Then according to the cam design theory,the angular displacement and angular quasi-acceleration of the cam follower is solved by using numerical computation method.Through comparing the value between angular quasi-acceleration and expected angular quasi-acceleration,the error of the angular quasi-acceleration is obtained,then the angular displacement error is solved.Through removing the angular displacement error,the cam theoretical profile compensation is carried out,and the data of discrete points more closer to the original design of cam profile line is acquired.Thus the scientific method for the reverse design of this kind of cam mechanism is provided.